Brief considerations on the genealogy and the meaning of the Recommendation on the protection and promotion of museums and collections, their diversity and their role in society Paris, 20 November 2015 (Cadernos de Sociomuseologia, 2017)
In May 2003, the National Museum Policy was launched in Brazil, by the initiative of the Ministry of Culture, led by Minister Gilberto Gil, during the first government of President Luiz Inácio Lula da Silva.